PABP1 Drives the Selective Translation of Influenza A Virus mRNA. Issue 5 (15th March 2022) - de Rozières, Cyrus M.; Pequeno, Alberto; Shahabi, Shandy; Lucas, Taryn M.; Godula, Kamil; Ghosh, Gourisankar; Joseph, Simpson
Graphical abstract: Highlights: The 5′UTRs of IAV mRNAs are highly conserved and adenosine rich. PABP1 binds to the viral 5′UTR and recruits eIF4G. mRNAs with viral 5′UTRs are resistant to cap-dependent translation inhibition. IAV mRNAs may use an alternative mechanism for translation initiation when cap-dependent translation is inhibited. Abstract: Influenza A virus (IAV) is a human-infecting pathogen with a history of causing seasonal epidemics and on several occasions worldwide pandemics. Infection by IAV causes a dramatic decrease in host mRNA translation, whereas viral mRNAs are efficiently translated. The IAV mRNAs have a highly conserved 5ʹ-untranslated region (5ʹUTR) that is rich in adenosine residues. We show that the human polyadenylate binding protein 1 (PABP1) binds to the 5′UTR of the viral mRNAs. The interaction of PABP1 with the viral 5ʹUTR makes the translation of viral mRNAs more resistant to canonical cap-dependent translation inhibition than model mRNAs. Additionally, PABP1 bound to the viral 5ʹUTR can recruit eIF4G in an eIF4E-independent manner. These results indicate that PABP1 bound to the viral 5ʹUTR may promote eIF4E-independent translation initiation.